1987
DOI: 10.1111/j.1398-9995.1987.tb02188.x
|View full text |Cite
|
Sign up to set email alerts
|

Antiallergic activity of loratadine, a non‐sedating antihistamine

Abstract: Loratadine is a new non-sedating antihistamine. The present studies compared loratadine and terfenadine, another non-sedating antihistamine, for their ability to inhibit the bronchial response to histamine and other autacoids which have been implicated as contributing to the symptoms of an allergic reaction. In addition, the two antihistamines were evaluated in models of immunologically mediated allergic reactions. Loratadine is a more potent inhibitor of histamine-induced bronchospasm in guinea pigs than is t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
31
1

Year Published

1988
1988
1996
1996

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(34 citation statements)
references
References 23 publications
2
31
1
Order By: Relevance
“…Cetirizine is effective in reducing antigen-induced nasal symp toms, and LTC4, but not histamine, release in nasal lavage fluids [23], An inhibitory effect of cetirizine on in vivo antigen-induced histamine and PAF-acether release in human skin has been described by Michel et al [24] and Charlesworth et al [25]. Loratadine can inhibit in vitro histamine and LTC4 release from rat and human lung mast cells [5][6][7][8], Terfenadine can inhibit in a dose-dependent manner the re lease of eicosanoids after challenge of dispersed human lung cells with anti-fgE [26] and can inhibit mediator re lease from human eosinophils [27], Furthermore, an inhib itory effect o f terfenadine on IgE-mediated histamine re lease from human basophils at concentrations of 1-2x 10 •' M [27] and from human lung mast cells at a concen tration of 10 ^ M [28] has been described.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cetirizine is effective in reducing antigen-induced nasal symp toms, and LTC4, but not histamine, release in nasal lavage fluids [23], An inhibitory effect of cetirizine on in vivo antigen-induced histamine and PAF-acether release in human skin has been described by Michel et al [24] and Charlesworth et al [25]. Loratadine can inhibit in vitro histamine and LTC4 release from rat and human lung mast cells [5][6][7][8], Terfenadine can inhibit in a dose-dependent manner the re lease of eicosanoids after challenge of dispersed human lung cells with anti-fgE [26] and can inhibit mediator re lease from human eosinophils [27], Furthermore, an inhib itory effect o f terfenadine on IgE-mediated histamine re lease from human basophils at concentrations of 1-2x 10 •' M [27] and from human lung mast cells at a concen tration of 10 ^ M [28] has been described.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in guinea pigs or rats sensitized to ovalbumin have demon strated that loratadine can block antigen-induced bronchoconstriction in a dose-dependent fashion [5], In vitro studies have shown that loratadine can inhibit histamine and leukotriene C4 (LTC4) release from rat and human lung mast cells [5][6][7][8]. The antiallergic activity of loratadine has also been reported in clinical studies in humans using skin prick tests [9] and nasal challenge methods [10,11], Basophils and mast cells are primary effector cells of type 1 allergic reactions, since they bear high-affinity IgE receptors on their membranes and release potent inflamma tory mediators, such as histamine and LTC4, following membrane IgE cross-linking by antigen [12,13].…”
Section: Introductionmentioning
confidence: 99%
“…Although it is well known that (1-adrenoceptor agonists do not inhibit mediator release from rat mast cells [16,17], (1-adrenoceptor agonists are potent inhibitors of histamine release in human lung fragments [6,7,18,19], dispersed human lung mast cells [9,20,21], human skin slices [19], dispersed human skin mast cells [4], and in in vivo studies of human skin [22][23][24], (1-adrencrgic receptor activation also inhibits antigen-induced peptidoleukotricne genera tion by human lung fragments [19] and dispersed lung mast cells [9,20,21], Ketotifen is a derivative of the tricyclic compound, benzocycloheptathiophcne, that differs markedly in its chem ical structure from any of the classic antihistamines [25,26], Ketotifen (10-200 \iM) inhibits histamine release from rat peritoneal mast cells using non-immunologic stimuli [27][28][29][30]. Ketotifen also inhibits the release of histamine and slow-reacting substance of anaphylaxis (SRS-A) leukotrienes from peripheral human leukocytes induced by both immunogenic (anti-IgE) and non-immunogenic (cal cium ionophore A23187) stimuli [31][32][33].…”
Section: Introductionmentioning
confidence: 99%
“…bronchus, nose and skin [7,8,20,22,23], Thus it appeared appropri ate to utilize this HI antagonist in a study of the LPR.…”
Section: Discussionmentioning
confidence: 99%
“…Loratadine also has demonstrated antiallergic activity, as shown by the drug's inhibition of the release of histamine as well as the production and re lease of prostaglandins (PGD2) and leukotricncs (LTC4) from mast cells [7,8,20,22,23]. Further, Loratadine has been reported in both animal models and in humans to protect against several allergic challenges, such as skin prick tests, nasal and bronchial challenges [7,8,20,22,23].…”
Section: Introductionmentioning
confidence: 99%